Análise comparativa de controladores MPPT aplicados a um sistema fotovoltaico - Confessor, Sâmya Lorena de Medeiros (Universidade Federal Rural do Semi-Árido, 2014)
The use of solar panels to generate electricity is something that is becoming more common comes in both large systems, as in autonomous systems with low power consumption. So that there is maximum utilization of energy generated, the panel must always operate at maximum power point (MPP). Based on this, this paper aim to perform a comparative study of two techniques for tracking the maximum power point MPPT (Maximum Power Point Tracking): the traditional method Perturbation and Observation (P&O) and the method by Fuzzy Logic. The photovoltaic system was modeled in ATLAB/Simulink® to represent the VI characteristic curve of the PV module, which is based on data available in the catalogs of commercial photovoltaic panels. From the results of the simulation study comparing control techniques, which showed that the fuzzy controller using the best performance and efficiency in keeping the MPP than the control technique based on the P&O was done
Comparative analysis of MPPT controllers applied to a photovoltaic system
Keywords: Photovoltaic system; Fuzzy logic; MPPT; Sistema fotovoltaico; Lógica fuzzy; MPPT; ENGENHARIAS::ENGENHARIA ELETRICA